Comparative Morphology of Dendrocometes paradoxus (Ciliophora, Suctorea) from two Distant Regions (Ukraine and Mexico) and Different Host Species - Dovgal, I.V.; Mayen-Estrada, R. (Вестник зоологии, 2013)
Comparative analysis of Dendrocometes paradoxus Stein, 1852 cell morphology from various gammarid amphipod species in different regions of Ukraine, and those attached to several host body parts of Hyalella azteca collected in two Mexican lakes, was carried out in order to demonstrate the morphological variability, due to the hosts species or their geographical distribution. For hosts species and corporal distribution, no significant differences between the two populations were shown. As the result, it was found the suctorians common for amphipod crustaceans from Ukraine and Mexico all are conspecific and belong to D. paradoxus. Приводятся результаты сравнительного анализа морфологии суктории Dendrocometes paradoxus Stein, 1852 из различных регионов Украины (с разных видов гаммарид) и с амфиподы Hyalella azteca, собранной в двух мексиканских озерах. Существенных отличий между особями инфузории с разных хозяев, при разной локализации на теле хозяев, а также связанных с географическим распространением хозяев, обнаружено не было. Таким образом, на амфиподах из пресных водоёмов Украины и Мексики обитает один вид сукторий – D. paradoxus.